2005
DOI: 10.1002/app.21287
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gelatin on the swelling behavior of organic hybrid gels based on N‐isopropylacrylamide and gelatin

Abstract: Organic hybrid gels based on poly(N-isopropylacrylamide) and a natural polymer, gelatin, were prepared through two-step crosslinking with genipin or glutaraldehyde. The effects of the gelatin content on the swelling behaviors and physical properties of these hybrid gels were investigated. The results indicated that the swelling ratio decreased with an increase in the content of gelatin in these hybrid gels. The swelling ratio for the gel crosslinked by genipin was significantly smaller than that for the gel cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…This was interpreted by assuming that the mixing free energy between polymer segments is not a linear function of the solvent composition. Similar behavior was also observed by Tanaka et al, Kim et al, Schild et al, Winnik et al, and in our previous study 29–33…”
Section: Resultssupporting
confidence: 92%
“…This was interpreted by assuming that the mixing free energy between polymer segments is not a linear function of the solvent composition. Similar behavior was also observed by Tanaka et al, Kim et al, Schild et al, Winnik et al, and in our previous study 29–33…”
Section: Resultssupporting
confidence: 92%
“…The reason might be that PEGMEA and gelatin are good water absorbents, as well as that full-IPNs usually provide more capacity to reserve the water. For the mechanical properties, the G values of hydrogels synthesized in this study were smaller than those reported [36]. Since G is related to the cross-linking density (ρ), NIPAAm with short and small branches may have led to a more compact structure of IPNs with high cross-linking density.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 54%
“…There have only been a few reports that discuss gelatin-based IPN hydrogels in the last five years; for example, the formation of semi-IPNs from N -isopropylacrylamide (NIPAAm) [36], the formation of full-IPNs from poly(acrylic acid) and gelatin [37], and the formation of full-IPNs from poly(2-hydroxyethylmethacrylate) (poly(HEMA)) and gelatin [38] have been reported. The IPNs based on PEGMEA and gelatin in our current study was full-IPNs.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…Gelatin based hydrogels are used in many applications, from ingredient of food preparation to innovative materials and biomaterials. Thermoreversible IPNs were prepared by addition of genipin or glutaraldehide to N-isopropylacrylamide/gelatin mixtures [287]. A rapid swelling/deswelling occurs when the temperature was cycled from The collagen-based materials with complex structures able to rebuild different shaped products, such as membranes, sponges, threads for surgical or dental purposes, and cell culture matrices, are obtained by different physical (electrospinning, molding, or additive manufacturing) or chemical procedures.…”
Section: Gelatinmentioning
confidence: 99%